Quality Aspects of Manually Transported Drinking Water in the Outskirts of Khartoum State (University of Khartoum Engineering Journal, 2022)
The main objective of this paper is to assess the quality of drinking water at the out skirts of Khartoum State. The objectives include studying the effects of practices employed by the inhabitants of Al-Hella Al-Jadeeda in handling, transporting and storing water. In addition to statistical analysis of data collected through questionnaires, samples from different sources and locations of wells, tanks, carro carts and drinking water containers, were collected and examined physically, chemically and microbiologically. The results revealed that, the water is physically and chemically acceptable for human consumption except for some doubts in its lead content. The lead content was found to be varied between 0.03 to 0.667 mg/L, which indicates a quantity far above the maximum allowable limits. Tests conducted on microbiological quality of water showed that water samples, were highly contaminated with coliform bacteria, which implies that fecal contamination is evident. It could be concluded that the pollution found is due to poor environmental sanitation awareness and carelessness of people on their personal hygiene. The study recommended that a network distribution system should be established in the area. Meanwhile, traditional drinking water carriers and distributors must be periodically cleaned, regularly disinfected with chlorine to remove any public health hazards. It is also recommended to introduce low-cost technologies such as sand purification systems in addition to the enhancement of awareness on the health hazards of polluted water.